Priority Mapping for Handling Environmental Road Using GIS in Gerung District, West Lombok Regency - Hafiz Hamdani; Pujiastuti, Heni (Fakultas Teknik Universitas Brawijaya, 2022)
Improving road access is very important to support human activities. One of them is improving the quality of environmental roads in Gerung District, West Lombok Regency. To make it with the availability of funds which cannot cover the entire segment in one time, that’s why priority handling is needed. This paper intends to determine the number of environmental roads in Gerung District; to know the priority of handling with SDI survey; and create a handling priority map using GIS. Based on the results, it was found that the number of environmental roads in Gerung District was 987 sections spread over 11 villages and 3 sub-districts. Handling priority of environmental road determined by the classification of road conditions as follows: good, medium, lightly damaged and heavily damaged. The number of roads based on this classification are: 568 segments for good condition; 131 segments for medium conditions; 200 segments for lightly damage; and 88 sections for heavily damaged conditions. In the map, each road segment assigned with colour identity according to its conditions and handling priorities using QGIS. The colour identities are: yellow for good condition; orange for medium conditions; red for lightly damaged conditions; and maroon for heavily damaged conditions.